Challenges of ethanol production from lignocellulosic biomass - Frazão, Cláudio José Remédios (2015)
The present work aimed to tackle two of the major challenges in bioethanol production from lignocellulosic feedstocks: (i) high tolerance of microorganisms to lignocellulosic inhibitors, and (ii) microbial contamination avoidance. Lignocellulosic inhibitors are an important fraction of spent sulphite liquor (SSL), a by-product of the pulp and paper industries. Hardwood SSL (HSSL) is rich in pentose sugars, mainly xylose, which can be converted to ethanol by the yeast Scheffersomyces stipitis. In this work, a population of S. stipitis previously adapted to 60 % (v/v) of HSSL was used, and its stability on the absence of inhibitors during ten sequential transfers was investigated at single-clone level. During the screening trials, all the isolated clones showed higher xylose and acetate uptake rates and lower ethanol productivities than the parental strain. The clone exhibiting higher xylose uptake rate (0.558 g L-1 h-1) was named isolate C4. The effect of short-term adaptation on isolate C4 fermentation performance was evaluated by pre-cultivating the clone in the presence or absence of 60 % (v/v) of HSSL. The uptake rates of glucose and xylose were similar under both conditions, but a higher acetate consumption rate (0.101 g L-1 h-1) and maximum ethanol concentration (4.51 g L-1) were achieved without pre-adaptation step, suggesting the robustness of isolate C4. The industrial bioethanol production is mostly carried out under non-sterile conditions, which favours microbial contamination. In this work, the mechanism that triggers Lactobacillus pentosus contamination in SSL plants was investigated. A simulated synthetic hydrolysate mimicking the average composition of sugars and inhibitors of softwood SSL (SSSL) was used and the impact of different factors in bacterial and Saccharomyces cerevisiae viability was analysed. The presence of yeast extract led to an increase in lactate production (9-fold higher) and L. pentosus viability when only bacteria was inoculated. Using different inoculation ratios of yeast/bacteria, the ethanol production rates were not affected after 48 h, and L. pentosus failed to overtake S. cerevisiae. The presence of inhibitors delayed yeast growth, but the bacteria did not outcompete S. cerevisiae. When the pH was optimal to L. pentosus in co-culture experiments, the bacterial cell viability decreased slower. The results indicate that L. pentosus was unable to overtake S. cerevisiae. The presence of yeast extract and favourable pH to bacteria are important factors that can play a role in the mechanism that triggers the bacterial contamination in ethanol plants.